Assessing the completeness of bryophyte inventories: an oceanic island as a case study (Terceira, Azorean archipelago) - Aranda, Silvia C. (2010)
How useful, complete or unbiased are comprehensive databases in order to provide reliable estimations of diversity? Using compiled data from bryophytes in Terceira Island (Azores), we specifically aim (1) to describe the register of species over time, (2) to assess the inventory completeness, i.e., the ratio between the observed and the maximum expected species, and (3) to locate the most promising areas for further surveys. First, each new recorded species was plotted against its collecting year, using the number of database-records as a surrogate of survey effort, to get the accumulation curves. These curves were then extrapolated to obtain the theoretical number of existing species according to Clench and exponential models. Spatial and habitat characteristics of the recorded taxa were also explored. Our results show an increasing trend in the rate of recorded species (c. five species per year), as well as a maximum of around a third of the theoretically “real” number of expected species that could yet remain unknown. Nevertheless, predictions of species richness were highly variable depending on the fitting curve used. Survey effort was similar between liverworts and mosses, as were inventory completeness values, but the rate of new recorded species was higher for mosses. Although bryologists visited preferably native habitats, we show that new species citations may also be found in modified habitats (e.g., exotic forests and semi-natural grasslands). We conclude that the analysis of extensive databases is a useful tool in revealing the recording and taxonomic gaps, further showing that bryophyte inventories could still be incomplete in Terceira Island. A strategy on how to improve species’ collections in remote areas is suggested, hoping to contribute to all-inclusive biodiversity studies in the Azores and elsewhere.